Chapter At the Intersection of Art, Architecture and Archaeology: 3D Virtualization and Contemporary Heritage - Maschner, Herbert D. G. (Proceedings e report, 2018)
We are at a global transition where disciplines from art to computer engineering intersect in the realm of global digital heritage. This has been facilitated by the development of desktop high-speed computing, inexpensive photogrammetry software, and digital photography. These technologies, and the tools to make them useful both in the lab and on the web, require the appropriate integration of technical skill, artistic license, archaeological background knowledge, and architectural realities.